2015
DOI: 10.1021/acs.jpcb.5b04556
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Solvation of Organic Ions II: Study of Linear Alkylated Carboxylate Ions in Water Nanodrops and in Liquid Water. Propensity for Air/Water Interface and Convergence to Bulk Solvation Properties

Abstract: We investigated the solvation of carboxylate ions from formate to hexanoate, in droplets of 50 to 1000 water molecules and neat water, by computations using standard molecular dynamics and sophisticated polarizable models. The carboxylate ions from methanoate to hexanoate show strong propensity for the air/water interface in small droplets. Only the ions larger than propanoate retain propensity for the interface in larger droplets, where their enthalpic stabilization by ion/water dispersion is reduced there by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(82 citation statements)
references
References 53 publications
12
70
0
Order By: Relevance
“…times smaller than those at m/z 431 (and 433) from OA at [1-octanol] = [OA] = 100 mM reveals that 1-octanol is much less reactive than OA toward CIs, although both species are expected to have similar affinities for aqueous surfaces. 25,32,43,[69][70] The C 23 ethers and esters produced in each case, by having similar mass and structures (see This finding is in line with gas-phase reaction rate constants of CIs + HCOOH/CH 3 COOH, which approach collisionally controlled values: k ≥ 10 -10 cm 3 molecule -1 s -1 , 22 vs. the much smaller values for CIs + methanol/2-propanol. 48,50,68 Tobias and Ziemann have reported that rate constants of gas-phase C 13 CIs reactions with various species increase in the order: water < methanol < 2-propanol < formaldehyde < formic acid < heptanoic acid, over a 10 4…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 65%
“…times smaller than those at m/z 431 (and 433) from OA at [1-octanol] = [OA] = 100 mM reveals that 1-octanol is much less reactive than OA toward CIs, although both species are expected to have similar affinities for aqueous surfaces. 25,32,43,[69][70] The C 23 ethers and esters produced in each case, by having similar mass and structures (see This finding is in line with gas-phase reaction rate constants of CIs + HCOOH/CH 3 COOH, which approach collisionally controlled values: k ≥ 10 -10 cm 3 molecule -1 s -1 , 22 vs. the much smaller values for CIs + methanol/2-propanol. 48,50,68 Tobias and Ziemann have reported that rate constants of gas-phase C 13 CIs reactions with various species increase in the order: water < methanol < 2-propanol < formaldehyde < formic acid < heptanoic acid, over a 10 4…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 65%
“…This arises from an inaccurate description of the water pairwise interactions corresponding to a particular water dimer conformation. In particular that yields the proton hydration enthalpy, Δ H hyd (H + ), extrapolated from halide or carboxylate/water nanodroplet data, to be from 3 to 8 kcal mol –1 weaker than the well accepted experimental range of values, while our TCPE/2013‐based Δ H hyd (H + ) estimate extrapolated from methylated ammonium/water nanodroplets is in much better agreement with experiment …”
Section: Introductionsupporting
confidence: 79%
“…NH4+/water interactions are modeled accordingly, i.e., we use the above dispersion term instead of a specific U mbp one (the above second sum then runs on ammonium centers). The carboxylate methyl and ammonium dispersion parameters are provided in our former studies …”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic molecules with long alkyl chains will reside more readily in the surface region, despite attached ionic functional groups. 7 , 39 The longer the alkyl chain, the more important hydrophobic interactions become that outweigh the hydrophilic–water interactions, resulting in a more similar surface enrichment of the charged and non-charged species, as seen for A6/A6H + , A4/A4H + and C5 – /C5H in Table 1 . For up to three carbon atoms in an alkyl chain, the hydrophilic interactions dominate the overall hydration behavior, yielding relatively large differences in the surface enrichment factors of a carboxylic acid and its conjugated carboxylate ion, see results on C4 – /C4H in Table 1 .…”
Section: Resultsmentioning
confidence: 97%